Manuale di batteriologia clinica Dalla teoria alla pratica in laboratorio - Rossetti, Roberto (Manuali - Biomedica, 2005)
The manual aims to represent the essence of bacteriology that is carried out in a medium-large sized clinical Microbiology laboratory, stating its operational aspects with simple, easily applicable schemes resulting from long experience